Active arc suppression device based on voltage‐source convertor with consideration of line impedance in distribution networks - Bishuang Fan (Wiley, 2021)
Abstract In the non‐effectively grounding distribution system, residual current under single‐line‐to‐ground (SLG) fault threatens the safety of human being and power supply equipment. Active arc suppression device has been proved to be effective for SLG fault arc suppression when the line impedance is ignored. However, in practice, line impedance varies with the fault location and the load current flowing through the impedance brings about additional voltage drop, which increases the fault current and is not dealt with by the conventional methods. To achieve accurate SLG fault arc suppression with the existence of line impedance, the neutral‐to‐ground voltage reference for full ground‐fault current compensation is firstly derived and a detection method is then proposed. The pre‐fault and post‐fault line currents are used to eliminate the influence of load current on the line impedance voltage drop. A dual‐loop voltage and current controller is then designed. The prototype of active arc suppression device was developed. The results of simulation and prototype experiment validate the effectiveness of the proposed method.